2015
DOI: 10.1053/j.ackd.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

GFR Estimating Equations and Liver Disease

Abstract: It is important to accurately assess the glomerular filtration rate (GFR) of patients with liver disease in order to deliver care and allocate organs for transplantation in a way that improves outcomes. The most commonly used methods to estimate GFR in this population are based on creatinine, which is biased by these patients’ low creatinine production and potentially by elevated serum bilirubin and decreased albumin levels. None of the creatinine based estimated GFR (eGFR) equations have been specifically mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 50 publications
0
42
1
3
Order By: Relevance
“…Furthermore, in patients who are obese (body mass index >30 kg/m 2 ), creatinine‐based eGFR calculation using the MDRD and CKD‐EPI estimates underestimated GFR, whereas cystatin C–based measurement did not . Finally, while results have been mixed, some studies show improved estimation of GFR in severe liver disease because creatinine is biased by low creatine production and elevated bilirubin in these patients …”
Section: Cystatin C For Staging Chronic Kidney Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in patients who are obese (body mass index >30 kg/m 2 ), creatinine‐based eGFR calculation using the MDRD and CKD‐EPI estimates underestimated GFR, whereas cystatin C–based measurement did not . Finally, while results have been mixed, some studies show improved estimation of GFR in severe liver disease because creatinine is biased by low creatine production and elevated bilirubin in these patients …”
Section: Cystatin C For Staging Chronic Kidney Diseasementioning
confidence: 99%
“…In another case report, dosing of an aminoglycoside antibiotic cleared by the kidney corrected for eGFR‐creatinine resulted in overestimation of GFR, accumulation of the drug, and, ultimately, AKI in an elderly man. The patient also sustained liver injury, and studies have shown that in advanced liver disease, use of creatinine leads to an overestimation of GFR . To remedy this, cystatin C is recommended for more accurate GFR estimation and dosing guidance .…”
Section: Recommendations For Renal Impairment Studies In Drug Developmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite its utility as a low‐cost and widely accessible estimate of renal function, eGFR does not assess the laterality of dysfunction, differentiate pathophysiology, or predict recovery. The equations in current use overestimate eGFR in patients with comorbid liver disease, and have poor accuracy in populations with renal dysfunction but normal eGFR; for example, early in the course of diabetes …”
mentioning
confidence: 99%
“…differentiate pathophysiology, or predict recovery. The equations in current use overestimate eGFR in patients with comorbid liver disease, 2 and have poor accuracy in populations with renal dysfunction but normal eGFR; for example, early in the course of diabetes. 3,4 Given the limitations of the established measures of renal function, there is a potential role for imaging.…”
mentioning
confidence: 99%